2011
DOI: 10.4161/cam.5.4.16986
|View full text |Cite
|
Sign up to set email alerts
|

The roles of amyloid precursor protein (APP) in neurogenesis

Abstract: The amyloid-beta (Aβ) peptide is the derivative of amyloid precursor protein (APP) generated through sequential proteolytic processing by β- and γ-secretases. Excessive accumulation of Aβ, the main constituent of amyloid plaques, has been implicated in the etiology of Alzheimer's disease (AD). It was found recently that the impairments of neurogenesis in brain were associated with the pathogenesis of AD. Furthermore recent findings implicated that APP could function to influence proliferation of neural progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 130 publications
1
52
1
Order By: Relevance
“…Overexpression of APP and BACE1 contribute to the formation of Aβ and participate in the aging process [17,18,31,32,33]. In this study, we found that the protein level of APP was elevated in both the forebrain cortex and hippocampus of the middle-aged rats compared to young rats (Fig.…”
Section: Resultssupporting
confidence: 56%
“…Overexpression of APP and BACE1 contribute to the formation of Aβ and participate in the aging process [17,18,31,32,33]. In this study, we found that the protein level of APP was elevated in both the forebrain cortex and hippocampus of the middle-aged rats compared to young rats (Fig.…”
Section: Resultssupporting
confidence: 56%
“…Although the exact pathogenesis of AD remains elusive, neurotoxicity of amyloid β peptide (Aβ) is considered a major factor in AD pathogenesis (Rajasekhar et al, 2015) and is closely related to impairment of neurogenesis in the AD brain (Zhou et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In the trophic factor deprivation paradigm, APP cleavage by Beta-site APP cleavage enzyme (BACE1) activates caspase-6 and caspase-3 pathways in axons and neuronal cell body, respectively (Vohra et al 2010, Nikolaev et al 2009). The accumulation of Aβ causes neuronal damage in Alzheimer’s disease (O’Brein & Wong 2011, Zhou et al 2011) and Aβ also contributes to the formation of intracellular neurofibrillary tangles, which further accelerates the process of neuronal loss and causes the symptoms of dementia (Takata & Kitamura 2012). …”
Section: Introductionmentioning
confidence: 99%